Long-lived Intermediates in Phytochrome Transformation II: In Vitro and In Vivo Studies - Briggs, Winslow R. (1969)
Conditions of illumination which cause phytochrome to cycle rapidly from P(R) to P(FR) and back lead to the accumulation in vivo of detectable amounts of long-lived intermediates on the P(R) to P(FR) pathway in oat coleoptile tissue. They appear to decay independently and in parallel to P(FR). Their behavior under different intensities of illumination and exposure time suggests that they are homologous with 2 similar intermediates previously observed in vitro. Available evidence favoring this suggestion is discussed. Equivalent illumination apparently causes far higher steady state levels of absorption by intermediates in vivo than in vitro, suggestion that native phytochrome is in a different physical state in the cell than it is in solution. A difference spectrum for the intermediates in vitro between 365 and 580 nm is presented. It has a maximum at 380 nm, a minimum at 418 nm, and crossover points at 398 and 485 nm. Glycerol in the phytochrome sample enhances the signal without otherwise changing the spectrum in any way. The difference spectrum represents the difference in absorption between the combined intermediates and P(FR).